Comparison of Quenching Kinetics and Mechanism of Tryptophan by Acrylamide and Genistein Studied by Fluorescence Spectroscopy - Phuong Ho; Dat Phat Nguyen; Khoi Dinh Dang; Hao Minh Hoang (Journal of Technical Education Science, 2025)
Fluorescence quenching using acrylamide and genistein as quenchers has been used to investigate the quenching kinetics and mechanism of tryptophan (Trp) monomer. Fluorescence quenching experiments of Trp by acrylamide were revised as references in present work. The in vitro inhibitory potential against α-glucosidase of genistein has been reported in previous literature, suggesting that the contacts of Trp residue of enzyme and genistein are responsible for the inhibitory activity of genistein. Therefore, genistein was selected as a quencher to symmetrically investigate the quenching kinetics and mechanism of Trp monomer in phosphate buffer pH 6.9. Prior to scanning fluorescence intensity of Trp solutions with (F) and without (Fo) quenchers in a wavelength range from 300-450 nm, fluorophore was excited at 295 nm. Consequently, the bimolecular quenching constants (kq) were graphically extracted from the Stern-Volmer plot of Fo/F versus quencher concentration [Q]. The values of kq for bimolecular quenching of Trp by acrylamide and genistein are 2.2´109 M-1s-1 and 2.0´1012 M-1s-1, respectively. These experimental results indicated that Trp was quenched by acrylamide through a dynamic quenching mode. Compared with acrylamide, the ground state formation, i.e., a static quenching process of Trp was dominant in the presence of genistein.